Promoting music intervention training in oncology in China: Challenges, opportunities, and pathways forward - Nie Juan; He Ying-Lan (Visualized Cancer Medicine)
Accumulating evidence confirms the effects of music-based interventions in alleviating the psychological burdens of cancer patients. However, the implementation and accessibility of such interventions within healthcare facilities for cancer patients in China remains limited. This article argues that the shortage of positions and the lack of formal career pathways for music therapists impede the wider application of music interventions. Although health professionals show great interest in implementing this emerging intervention, they often lack the foundational knowledge and essential skills, which diminishes its effectiveness. This viewpoint calls for tailored training that equips health professionals with basic skills to practice basic music interventions at a supportive level to satisfy patient care needs while promoting ongoing collaboration between medical personnel and credentialed music therapists. It also advocates for increased investment in music therapists, standardized clinical procedures, and sustainable financial resources to accelerate the integration of music-based interventions into healthcare practices.